2017
DOI: 10.4317/jced.53668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Percentages of Microhydroxyapatite on Microhardness of Resin-modified Glass-ionomer and Zirconomer

Abstract: BackgroundHydroxyapatite (HA) is the main mineral component of the tooth structure, which exhibits considerable biological behavior and its incorporation might improve microhardness of dental materials. Microhardness of restorative materials, like glass-ionomer, is critical for the clinical longevity of restorations. The aim of this study was to evaluate the microhardness of two glass-ionomers types by incorporating different percentages of microhydroxyapatite.Material and MethodsIn this study, 80 disc-shaped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…The recorded improved mechanical properties of the Fuji II group after incorporating 10 wt% HA and associated improvements in FS probably resulted from the 'umbrella phenomenon of resin polymer' that protects the calcium polyacrylates from dissociation in the early phase of the setting, before maturation and the formation of more stable aluminum polyacrylates [1]. It was indeed shown that resin-modified GICs are more stable in a wet and acidic environment than are conventional GICs [31,32]. However, unlike conventional GICs, restorative materials containing resin have been shown to have negative effects on dental pulp; they also exhibit cytotoxicity, and they prompt biofilm formation and secondary caries development [33].…”
Section: Discussionmentioning
confidence: 96%
“…The recorded improved mechanical properties of the Fuji II group after incorporating 10 wt% HA and associated improvements in FS probably resulted from the 'umbrella phenomenon of resin polymer' that protects the calcium polyacrylates from dissociation in the early phase of the setting, before maturation and the formation of more stable aluminum polyacrylates [1]. It was indeed shown that resin-modified GICs are more stable in a wet and acidic environment than are conventional GICs [31,32]. However, unlike conventional GICs, restorative materials containing resin have been shown to have negative effects on dental pulp; they also exhibit cytotoxicity, and they prompt biofilm formation and secondary caries development [33].…”
Section: Discussionmentioning
confidence: 96%
“…It has been previously demonstrated that the incorporation of 15 wt% of micro-HAP into RMGIC improves microhardness, while the addition of 15 wt% of HAP has a negative effect on the microhardness of RMGIC. [13] Therefore, 15 wt% of micro-HAP was incorporated into a conventional GIC and a RMGIC in the present study. The bioactive hydroxyapatite (HAP)/zirconia-filled GIC demonstrated increased DTS and compressive strength compared to the unmodified GIC in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that HAP incorporation can interfere with the complete reaction of the components of RMGIC which can negatively affect the DTS. [13] However, the probable effects of different concentrations and different particle sizes of the HAP on mechanical and bond strength properties of GICs should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations